Refractive Predictability After Keratorefractive Lenticule Extraction Using a New Nomogram Creation Software Tool Compared to a Matched Control - Wan Q; Wei R; Tang J; Deng YP; Ma K (Clinical Ophthalmology)
Qi Wan, Ran Wei, Jing Tang, Ying-ping Deng, Ke Ma Department of Ophthalmology, West China Hospital of Sichuan University, Chengdu, People’s Republic of ChinaCorrespondence: Ying-ping Deng, Department of Ophthalmology, West China Hospital of Sichuan University, #37, Guo Xue Lane, Chengdu, Sichuan, 610041, People’s Republic of China, Email dyp_wch@163.com Ke Ma, Department of Ophthalmology, West China Hospital of Sichuan University, #37, Guo Xue Lane, Chengdu, Sichuan, 610041, People’s Republic of China, Email drmake@scu.edu.cnPurpose: The study aimed to assess the impact of VISULYZE nomogram software on refractive outcomes after lenticule extraction for myopia and myopic astigmatism correction.Methods: This ambispective, single-site, matched case–control study was conducted at West China Hospital in Chengdu, China. Treatments using the VISULYZE nomogram were compared to a control group without it. The main outcome was refractive accuracy at 3 months, measured by the proportion of eyes achieving a spherical equivalent (SEQ) within ± 0.50 D of the target and astigmatism ≤ 0.50 D.Results: The study involved 180 eyes, with 90 treated using VISULYZE and 90 matched controls analyzed retrospectively. In the VISULYZE group, 98.9% achieved SEQ within ± 0.50 D versus 85.6% in the control group (P< 0.001). Astigmatism ≤ 0.50 D was achieved in 100% of VISULYZE-treated eyes compared to 93.3% in controls (P=0.006). Both groups had similar safety indices. VISULYZE showed higher correlations between attempted and achieved SEQ (R²=0.9799) and astigmatism (R²=0.8996) compared to the control group (SEQ: R²=0.9590; Astig: R²=0.5992). Standard efficacy and safety measures showed no difference between groups.Conclusion: The VISULYZE-generated nomogram demonstrated improved predictability and accuracy in refractive outcomes. It may enhance results for surgeons compared to those using no nomogram or a standard offset nomogram.Keywords: lenticule extraction, outcomes, nomogram, VISULYZE, SMILE